Multiple aspects of matrix stiffness in cancer progression - Mancini, Alessandro; Gentile, Maria Teresa; Pentimalli, Francesca; Cortellino, Salvatore; Grieco, Michele; Giordano, Antonio (Frontiers in Oncology, 2024)
The extracellular matrix (ECM) is a complex structure present in every tissue and extremely active in guaranteeing the correct tissue homeostasis. It is constantly subjected to processes of remodeling, repair and renewal. Cell-ECM interactions are crucial in the processes of differentiation, proliferation, migration and invasion. The entire ensemble of genes encoding the proteins associated with the ECM is called matrisome. There are approximately 1,100 genes in the matrisome of human tissues. In tumors the ECM becomes highly dysregulated, fibrotic, playing both pro-tumorigenic and anti-tumor roles. In this review, we focused on the regulation of tumor progression and related phenomena by non-cell autonomous, environmental external factors linked to the qualitative and quantitative variations of the ECM.